Percutaneous cystolitholapaxy: A safe and effective alternative to open stone surgery for the management of complex bladder stones in patients with no urethral access. (March 2020) - Goldsmith, Louise; Neal, Naomi; Briggs, James; Tapping, Charles; Boardman, Phil; Turney, Ben; Reynard, John
Objectives: Bladder stone management in patients with reconstructed bladders drained by Mitrofanoff catheterizable channels, with no urethral access, generates multiple challenges. Trans-Mitrofanoff access limits the size of endoscopic stone fragmenting devices, risking prolonged procedures, incomplete stone clearance and damage to the continent conduit. Access through previous surgical access sites risks bowel injury. This case series reports outcomes in patients undergoing percutaneous cystolitholapaxy (PCCL), using ultrasound-guided access and direct track closure, thereby limiting radiation exposure and avoiding suprapubic catheters (SPCs). Patients and methods: Seven PCCL procedures were performed in five patients with closed urethras. Average age 32 years, primary diagnoses: spina bifida, vertebrae, anus, trachea, esophagus, renal (VATER) syndrome, bladder exstrophy and traumatic brain injury. Four used Mitrofanoff stomas and one an SPC. Average largest stone was 18.57 mm (range 10–30 mm). Five procedures were for multiple stones (range 2–30 stones). Results: Each PCCL achieved complete stone clearance. Average operative time: 146 min (range 72–250 min). No intraoperative blood loss or bladder perforation. Postoperative median length of stay was 2 days. Conclusion: PCCL is a safe, minimally invasive alternative to open surgery for large and multiple bladder stones in individuals with complex lower urinary tract anatomy, specifically reconstructed bladders drained by Mitrofanoff catheterizable channels with no urethral access. Level of evidence: Level 4